Dual inhibition of EZH2 and G9A/GLP histone methyltransferases by HKMTI-1-005 promotes differentiation of acute myeloid leukemia cells - Sbirkov, Y.; Schenk, T.; Kwok, C.; Stengel, S.; Brown, R.; Brown, G.; Chesler, L.; Zelent, A.; Fuchter, M. J.; Petrie, K. (Frontiers in Cell and Developmental Biology, 2023)
All-trans-retinoic acid (ATRA)-based differentiation therapy of acute promyelocytic leukemia (APL) represents one of the most clinically effective examples of precision medicine and the first example of targeted oncoprotein degradation. The success of ATRA in APL, however, remains to be translated to non-APL acute myeloid leukemia (AML). We previously showed that aberrant histone modifications, including histone H3 lysine 4 (H3K4) and lysine 27 (H3K27) methylation, were associated with this lack of response and that epigenetic therapy with small molecule inhibitors of the H3K4 demethylase LSD1/KDM1A could reprogram AML cells to respond to ATRA. Serving as the enzymatic component of Polycomb Repressive Complex 2, EZH2/KMT6A methyltransferase plays a critical role in normal hematopoiesis by affecting the balance between self-renewal and differentiation. The canonical function of EZH2 is methylation of H3K27, although important non-canonical roles have recently been described. EZH2 mutation or deregulated expression has been conclusively demonstrated in the pathogenesis of AML and response to treatment, thus making it an attractive therapeutic target. In this study, we therefore investigated whether inhibition of EZH2 might also improve the response of non-APL AML cells to ATRA-based therapy. We focused on GSK-343, a pyridone-containing S-adenosyl-L-methionine cofactor-competitive EZH2 inhibitor that is representative of its class, and HKMTI-1-005, a substrate-competitive dual inhibitor targeting EZH2 and the closely related G9A/GLP H3K9 methyltransferases. We found that treatment with HKMTI-1-005 phenocopied EZH2 knockdown and was more effective in inducing differentiation than GSK-343, despite the efficacy of GSK-343 in terms of abolishing H3K27 trimethylation. Furthermore, transcriptomic analysis revealed that in contrast to treatment with GSK-343, HKMTI-1-005 upregulated the expression of differentiation pathway genes with and without ATRA, while downregulating genes associated with a hematopoietic stem cell phenotype. These results pointed to a non-canonical role for EZH2, which was supported by the finding that EZH2 associates with the master regulator of myeloid differentiation, RAR, in an ATRA-dependent manner that was enhanced by HKMTI-1-005, possibly playing a role in co-regulator complex exchange during transcriptional activation. In summary, our results strongly suggest that addition of HKMTI-1-005 to ATRA is a new therapeutic approach against AML that warrants further investigation.